2003
DOI: 10.1021/la034032m
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Attachment of Poly(ethylene glycol) to Surfaces, Critical for Reducing Bacterial Adhesion

Abstract: The effects of different poly(ethylene glycol) (PEG) attachment strategies upon the adhesion of a Gramnegative bacteria (Pseudomonas sp.) was tested. PEG was covalently immobilized, at the lower critical solution temperature of PEG, to a layer of branched poly(ethylenimine) (PEI). PEI was both physically adsorbed to a stainless-steel (SS) substrate and covalently immobilized to a carboxylated poly(ethylene terephthalate) (PET-COOH) surface. On both substrates, the PEI and PEG grafting conditions were optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
229
2
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(243 citation statements)
references
References 51 publications
9
229
2
3
Order By: Relevance
“…37,40,56 The second approach allows for considerably better control of the thickness and functionality of the formed coatings.…”
Section: Considerations In the Strategy For Surface Derivatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…37,40,56 The second approach allows for considerably better control of the thickness and functionality of the formed coatings.…”
Section: Considerations In the Strategy For Surface Derivatizationmentioning
confidence: 99%
“…Covalent attachment of layers of poly-and oligoethylene glycols to various solid substrates, indeed, presents a broadly chosen approach for engineering of nonfouling interfaces. 3,37,40,43,48,67 PEGylated surfaces demonstrate some of the highest protein resistance; they are relatively durable; and chemically, PEGs are relatively easy to manipulate. 40,52,58 Utilizing self-assembled monolayers (SAMs) of alkylthiols on gold surfaces for engineering of bioactive interfaces has gained significant popularity due to the simplicity of the used chemistry 45,74 and to the availability of high-resolution structural information for such SAMs.…”
Section: Introductionmentioning
confidence: 99%
“…on PEG-grafted surfaces by Kingshott et al [5], S. aureus on oligo(ethylene glycol) (OEG) self-assembled monolayers (SAMs) by Cooper and Tegoulia [6], and for S. aureus and S. epidermidis on OEG SAMs by Ostuni et al [7]. Recently, various factors influencing microbial adhesion to PEG brushes (i.e., PEG chain length and adsorbed protein) were systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…7 Studies have shown that covalently immobilized PEG coatings provide superior antifouling properties, probably since they cannot easily be displaced by biomolecules or conditioning layer molecules. 9 PEG functionalization techniques can be broadly classified into "grafting to" and "grafting from" approaches. The grafting from technique generally gives higher graft density since the limiting factor is diffusion of monomer onto the reactive ends of growing chains, whereas in the case of the grafting to technique the limitation is diffusion of entire polymer chains to the reactive substrate.…”
Section: Introductionmentioning
confidence: 99%